GAMBARAN KARAKTERISTIK PENGGUNAAN KONTRASEPSI PADA WANITA YANG MENGALAMI KEHAMILAN TIDAK DIINGINKAN DI JAWA: ANALISIS PENDAHULUAN - Nohan Arum Romadlona (Jurnal Keperawatan Terapan, 2023)
Unwanted pregnancies have consequences for women's health. Unwanted pregnancies are a strong reason for women to have unsafe abortions which contribute to maternal mortality. The use effective contraception is one of the efforts to prevent unwanted pregnancies. This study was conducted to see an initial description of the characteristics of contraceptive use in women based on their desire to get pregnant. The results of the descriptive analysis show that 12.8% of women in Java in 2018 experienced unwanted pregnancies. Where they tend to have less good contraception knowledge than women who do not experience unwanted pregnancies. Most are described as using modern contraception and having less support from their husbands. The use of effective modern contraception is relatively small (25%) which has an impact on the still high rate of contraceptive failure. Increased use of modern contraception and access to rights-based family planning programs will increase the prevalence rate of contraceptive use and have an impact on reducing the number of unwanted pregnancies and the incidence of abortion.